Compost and Mycorrhizal Application on Longkida (Nauclea orientalis) Seedling at Post-Mining Soil PT. ANTAM Pomalaa PEMANFAATAN KOMPOS DAN MIKORIZA ARBUSKULA PADA LONGKIDA (Nauclea orientalis) DI TANAH PASCA TAMBANG NIKEL PT. ANTAM POMALAA - Ekawati .; Irdika Mansur; Panca Dewi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
The aims of this study were to analyze the effect of compost inoculated with arbuscular mycorrhizal fungi (AMF) on plant growth and the heavy metal accumulation capability of nickel post-mining soil, analyze the heavy metal accumulation capability of N. orientalis and to analyze the heavy metal concentrations before and after treatment in soil collected from a nickel mining PT. ANTAM Pomalaa. The experimental design used in this study was Completely Randomized Design with 5 replications. The treatment of this study was the ratio of soil and compost inoculated with arbuscular mycorrhizal fungi (AMF) by 75:25, 50:50 and 25:75, respectively. The results showed an effect of the addition of compost inoculated with AMF on plant growth. The highest growth on the ratio of soil and compost inoculated with AMF by 25: 75 and the lowest growth on the ratio of soil and compost inoculated with AMF by75: 25. The reduction of heavy metal concentration in the soil after treatment for Cr, Ni, Mn, Fe and Zn was 95.82%, 85.54%, 92.98%, 99.25% and 94.09%, respectively. The highest heavy metals concentration (Cr, Ni, Mn, Fe and Zn) in N. orientalis was on the treatment without compost inoculated with AMF and the lowest concentration was on the compost inoculated with AMF treatment by 25:75 ratio. Accumulation of heavy metals found in both the root and in the leaves of plant. The highest heavy metals concentration found in the root. Generally, the best treatment was the compost inoculated with AMF by 25:75 ratio.Key words: arbuscular mycorrhizal, compost, heavy metals, N. Orientalis, phytoremediation.